Respuesta :
you can solve this 2 ways: plug in all of the options or solve for x.
i going to solve for x.
given: x^2+2x=24 (subtract 24 on both sides to get make it look like x^2+x+1)
x^2+2x-24=0 (now factor x^2+2x-24 out)
x^2+2x-24 --> (x-4)(x+6)
new equation: (x-4)(x+6)=0 (now make them both equl zero)
new equaions: x-4=0 x+6=0 (now solve for x for both)
x-4=0 x+6=0
x=4 x=-6
your answer is 4 and -6.
if you were not taught how to do what i just did then i can message you how to plug those numbers into x^2+2x=24 to find the answer.
i going to solve for x.
given: x^2+2x=24 (subtract 24 on both sides to get make it look like x^2+x+1)
x^2+2x-24=0 (now factor x^2+2x-24 out)
x^2+2x-24 --> (x-4)(x+6)
new equation: (x-4)(x+6)=0 (now make them both equl zero)
new equaions: x-4=0 x+6=0 (now solve for x for both)
x-4=0 x+6=0
x=4 x=-6
your answer is 4 and -6.
if you were not taught how to do what i just did then i can message you how to plug those numbers into x^2+2x=24 to find the answer.
Answer:
The answer is c
Step-by-step explanation:
Correct on e2020